2017
DOI: 10.1080/09505431.2017.1300641
|View full text |Cite
|
Sign up to set email alerts
|

Special Treatment? Flexibilities in the Politics of Regenerative Medicine’s Gatekeeping Regimes in the UK

Abstract: Emerging flexibilities are apparent in gatekeeping regimes applicable to regenerative medicine products, raising issues about the extent to which and forms in which such flexibilities might promote emerging products as a sector warranting special treatment, in the context of recent policy developments in the UK and wider European Union. Concepts of 'gatekeeping', 'gatekeeping regimes' and 'gateways' can point to the ways in which regulatory institutions, health technology assessment organisations, and national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Small patient numbers are especially difficult for under-resourced SMEs running either the virtual or early exit Phase I/II business models because they cannot afford to recruit patients outside of the United Kingdom. However, Faulkner 16 reported that regulatory systems are now being adapted for rare indications, and Mittra et al 17 argue that the usual approach for indications such as b-thalassemia is to choose a country with a patient population sufficient for the clinical trial.…”
Section: Limited Patient Numbers For Clinical Trialsmentioning
confidence: 99%
“…Small patient numbers are especially difficult for under-resourced SMEs running either the virtual or early exit Phase I/II business models because they cannot afford to recruit patients outside of the United Kingdom. However, Faulkner 16 reported that regulatory systems are now being adapted for rare indications, and Mittra et al 17 argue that the usual approach for indications such as b-thalassemia is to choose a country with a patient population sufficient for the clinical trial.…”
Section: Limited Patient Numbers For Clinical Trialsmentioning
confidence: 99%
“…The flexible enforcement of regulatory standards in emerging fields of medicine research in China and India has also been interpreted as an attempt by national governments to stimulate domestic innovation, by facilitating clinical research that is affordable to local researchers and companies (Salter, 2008;Sleeboom-Faulkner et al, 2016;Sleeboom-Faulkner, 2016). Other developments, such as the surfacing of new types of regulatory exceptions and exemptions in the EU, and increasing access to experimental products in the USA, are partly the outcome of pressure from patient and consumer organizations, and partly a result of criticism from professional organizations that seek to enable more localized, physician-based forms of innovation (Cooper and Waldby, 2014;Faulkner, 2017;Rosemann et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These arguments, Montgomery suggests, have facilitated a move away from standardization as the central logic of clinical trials, towards an acceptance of adaptation, which promises 'predictable uncertainty' and the possibility of 'fixing the future' as it unfolds. Alex Faulkner's paper explores the extent to which and forms in which regulatory agencies in the European Union (EU) have started to introduce flexibilities to the standard regulatory pathway for market approval of medicinal products, which involves the mandatory use of multi-phase RCTs (Faulkner 2017; this special issue). Based on a case study of EU regulations for advanced cells and tissue products, he discusses a range of regulatory exceptions and exemptions that allow investigators and research sponsors either to shorten and accelerate the multi-phase RCT process, oras with the EU 'hospital exemption scheme'to provide access to innovative (but unproven) medical interventions without preceding trials.…”
Section: The Emergence Of New Forms and Spaces Of Alter-standardizationmentioning
confidence: 99%
“…As the geographical ties of these organizations illustrate, transnational opposition to the use of RCTs as the obligatory passage-point for market approval of stem cell technologies is increasing, even in the United States and Western Europe. In a context of intense global competition over markets and technological innovation, concerns about losing out, along with increasing health-care costs and the recent economic crisis, have resulted in calls for deregulation, more flexible regulations, and new spaces of regulatory exceptions and exemptions ( Cooper and Waldby, 2014 ; Faulkner, 2014 ). Moreover, stem cell controversies and regulatory changes affect regulatory debates and processes in other areas of medical research.…”
Section: The Emergence Of Transnational Network Of Alter-standardizamentioning
confidence: 99%